Length-Weight Relationships and Condition Indices of Reef Fishes Caught by bobo Fish Traps in Barangay Bato, Santa Cruz, Davao Del Sur, Philippines - Darrell Alcando (Research Aspects in Biological Science Vol. 3, 2022)
Length-weight relationships (LWR) are an important fisheries tool used in estimating stock biomass. The b parameter from LWR establishment also gives information to the pattern of growth of the fish living in a certain area or environment. The data in LWR in turn are useful in estimating fish conditions. Thus, this study is aimed to determine LWR and condition indices of reef fishes to determine growth patterns as well as conditions of fish which are considered as important information for any given fishery. The reef fishes obtained using bobo fish traps throughout the sampling period were identified and submitted to length-weight relationship analysis as well as the construction of condition indexes. The findings revealed that bobo fish traps were related with 16 species belonging to 9 groups in the study area. The establishment of length-weight relationship for fourteen species indicated that they all grew allometrically in which ten (10) species out of the 14 attained negative allometric growths while the remaining 4 species attained positive allometric growths indicating that most of the fish becomes less round or slender as they grow in length. The condition index (relative weight) of the 10 species studied in this study was greater than 100%, suggesting that they gained more weight than the observed population. Based on these data, it was determined that only a small number of reef fish species in the area were related with the bobo fishing approach. The negative allometric growths obtained by majority of the species indicated that the specimens are likely to encounter food scarcity. Regardless of potential threats to food resources, the results of the condition index analysis may suggest an overall healthy habitat for the fishes. Nonetheless, the perplexing result reflects the difficult-to-extrapolate, complicated interaction of fish growth with environmental changes.